Analyzing the Effects of Fiscal Policy On Income Distribution: A Comparison Between Developed and Developing Countries - Balseven, Hale; Tugcu, Can Tansel (International Journal of Economics and Financial Issues, 2017)
The study examines the effect of fiscal policy on income distribution in developed and developing countries. The study analyzes the explanatory power of tax and transfers on income inequality in 17 developing and 30 developed countries in between 1990 and 2014 by using linear panel data estimation techniques. According to the findings, tax revenues decrease income inequalities in developing countries while social benefits decrease income inequality in developed countries. Also, the economic growth has negative impact on income distribution in developing countries whereas the economic growth and inflation have positive impact on income distribution in developed countries. Keywords: Fiscal policy, Income distribution, Tax and expenditure policy. JEL Classifications: D63, D31, H20.